2015
DOI: 10.20493/bt.31618
|View full text |Cite
|
Sign up to set email alerts
|

Suriyelilerin Ekonomik Etkisi: Kilis İli Örneği

Abstract: Ülkelerinden kaçarak gelen Suriyelilerin Kilis ili sınırı içerisine yerleşmeleri, sosyal, ekonomik, ticari hayata katılmaları, Kilis'te yaşayan yerli halk, esnaf, işadamı, memur, işçi, öğrenci, eğitimci, hane halkı vs. için birtakım sosyal, ekonomik, ticari sonuçlar doğurmuştur. Bu sonuçlar Kilis'te yaşayan halkı önemli bir oranda etkilemektedir. Suriyeli sığınmacıların Kilis ili içerisinde ikamet etmeleri sonucunda oluşan iktisadi, ticari ve sosyal yaşamına etkilerini araştırmak, yerli halkın bu boyutlar üzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…The regulations also allow these migrants to start their businesses with the help of micro-credits granted by the Turkish government. Despite this, a significant number of Syrian migrants under temporary protection continue to work illegally [29]. This is confirmed by our study, since almost all of the participants reported to work in the informal sector.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…The regulations also allow these migrants to start their businesses with the help of micro-credits granted by the Turkish government. Despite this, a significant number of Syrian migrants under temporary protection continue to work illegally [29]. This is confirmed by our study, since almost all of the participants reported to work in the informal sector.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…has experienced several problems for this reason (Oytun, 2014) As a result of its proximity to Aleppo, Kilis has become a province where Syrians have stayed with their relatives, or rented or bought houses (Paksoy, Kocarslan, Kılınc, and Tunc, 2015). Having migrated to Turkey with their families and residing there, asylum seekers can earn their keep by working as helpers for artisans from various occupational groups, as qualified employees in industry, or working in businesses operated by themselves, especially in the food sector (Cengiz, 2015).…”
mentioning
confidence: 99%
“…Such cases have led to a number of social, economic, and commercial results for the native population, artisans, businessmen, officers, workers, students, trainers, households, etc. (Paksoy, Kocarslan, Kılınc, and Tunc, 2015).…”
mentioning
confidence: 99%
“…27 Paksoy ve arkadaşları ise Kilis'de yaptıkları çalışmada yerel halkın sağlık başta olmak üzere bazı kamu hizmetlerinden yararlanmada aksaklık yaşadığını ancak Suriyelilerin devlet kurumlarından sağlık hizmeti alma oranının sadece %3 olarak tespit edildiğini ifade etmişlerdir. 28 Sığınmacıların sunulan hizmetlerden yararlanmakta güçlük çektiği düşüncesi de yaşanılan sorunlardan bir tanesidir. Yapılan bir araştırmaya göre; Suriyelilerin kayıtlı oldukları ilde sağlık hizmetlerine ücretsiz bir şekilde kolay erişebildikleri ama kayıtlı oldukları il dışında erişimde problemler yaşadıkları savunulmuştur.…”
Section: Türkiye'de Sığınmacılara Yönelik Sağlık Politikalarıunclassified
“…29 Kördeve tarafından yapılan araştırmada Kocaeli Darıca bölgesinde yaşayan Suriyeli mültecilerin sağlık hizmetlerine erişimde ciddi bir problem yaşamadıkları tespit edilmiştir. 30 Ancak Paksoy ve arkadaşları yaptıkları çalışmada Suriyelilerin sağlık hizmetlerini yeterli düzeyde alamadıklarını ifade ederken 28 , Barın yaptığı çalışmada özellikle Suriyeli kadınlar için sağlık hizmetlerine erişimin bir problem olduğunu savunmuştur. 31…”
Section: Türkiye'de Sığınmacılara Yönelik Sağlık Politikalarıunclassified